"Fool me once, …": deception, morality and self-regeneration in decentralized markets. Issue 48 (2nd April 2019) - Gomes, Orlando; Frade, João
Abstract : Purpose: This paper aims to provide an overall review and assessment of the virtues and flaws of decentralized self-regulated markets, discussing in particular the extent to which deceiving attitudes by some market participants might be potentially diluted and contradicted. Design/methodology/approach: To approach deception and morality in markets, the paper follows two paths. First, the relevant recent literature on the theme is reviewed, examined and debated, and second, one constructs a simulation model equipped with the required elements to discuss the immediate and long-term impacts of deceiving behaviour over market outcomes. Findings: The discussion and the model allow for highlighting the main drivers of the purchasing decisions of consumers and for evaluating how they react to manipulating behaviour by firms in the market. Agents pursuing short-run gains through unfair market practices are likely to be punished as fooled agents spread the word about the malpractices they were allegedly subject to. Research limitations/implications: Markets are complex entities, where large numbers of individual agents typically establish local and direct contact with one another. These agents differ in many respects and interact in unpredictable ways. Assembling a concise model capable of addressing such complexity is a difficult task. The framework proposed in this paper points in the intended direction. Originality/value: The debate in this paper contributes to a stronger perception on the mechanisms that attribute robustness and vitality to markets.